Contribution of Investment Efficiency in the Relationship of Free Cash Flow and Firm Value at Indonesia Stock Exchange - Hiya, Nirmadarningsih; Syafi’i, Muhammad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The objective of this research is to examine the mediation effect of investment efficiency (ROA) and the moderation effect of Syariah in the relationship of free cash flow on firm value (Tobin q). Research population involved all manufacturing companies at Indonesia Stock Exchange on period 2012-2018. Purposive sampling was used as sampling technique and the obtained sample was 36 companies with total observation of 252. Hypothesis test was conducted with PLS-SEM analysis technique supported by software WarpPLS 5.0. Type of data was data panel with observation period from 2012 to 2018. Several empirical results were obtained. First, free cash flow has positive and significant effect on firm value. Second, free cash flow has positive and significant effect on investment efficiency. Third, investment efficiency has positive and significant effect on firm value. Fourth, Syariah does not have moderation effect in the relationship of free cash flow on firm value. Last, investment efficiency mediates partially the effect of free cash flow on firm value. From these results, several conclusions were made. Firm value can be indirectly affected through intervening variable. Mediation role played by investment efficiency informs that investment efficiency proxied by ROA can alleviate the contradictive results of empirical studies (research gap) concerning the effect of free cash flow on firm value.